Comprehensive investigation into dental pulp repair: from inflammatory mediators to macrophage polarization and extracellular matrix dynamics - Sousa, Alice Corrêa Silva (2024)
Concepts of tissue engineering and regenerative medicine have been based on new perspectives of therapeutic modalities for teeth with pulp necrosis and incomplete root formation aiming the regeneration of pulp tissue. In this way, studies have been carried out with the aim of identifying bioactive materials and techniques that allow the regeneration of the pulp tissue, structurally composed of vessels, nerves, and a wide variety of cells at different stages of differentiation. Thus, the general aim of this study was to evaluate the effects of bioactive endodontic and restorative materials in the synthesis of inflammatory and repair mediators and to understand the role of perivascular cells in detecting the mechanical state of the extracellular matrix in homeostasis and disease. Specifically, (1) it was evaluated, in vivo, the synthesis of inflammatory and repair mediators in pulp repair after capping with mineral trioxide aggregate (MTA) and then (2) the effect of bioactive materials in cultured macrophages and how dental stem pulp cells would respond when stimulated the secretome obtained from inflammatory cells. Also, (3) hydrogels with different molecular weights and percentages of methacrylamide were characterized and evaluated, in vitro, whether the fine adjustment of hydrogel stiffness could control the polarization of macrophages by regulating the M1/M2 phenotype of the cells at the repair site. Finally, (4) a single-channel on-a-chip microfluidic device was engineered to investigate the role of perivascular cells in detecting the mechanical state of the extracellular matrix in homeostasis and disease. We found that pulp capping with MTA resulted in mineralized tissue formation and the underlaying dental pulp presented higher synthesis of interleukin-1β, vascular endothelial growth factor, and platelet endothelial cell adhesion molecule-1 produced by resident and inflammatory cells. In vitro, bioactive materials did not impact on macrophage viability and differently activated the inflammatory cells. The secretome obtained from macrophages treated with BiodentineTM, MTA, calcium hydroxide, KETACTM glass ionomer cement and Beautiful composite resin induced mineralization mediators synthesis by dental pulp cells. We also described the development of nanobody-laden photocrosslinkable hydrogel using gelatin methacryloyl (GelMA) and provide proof-of-principle evidence that it is possible to release nanobodies from hydrogel that maintain their effects. Interestingly, we demonstrate that the fine adjustment of the stiffness modulates macrophage polarization towards the M2 phenotype. Finally, a single-channel on-a-chip microfluidic device was engineered and our results demonstrate, for the first time, that perivascular cells may be critical mediators of important events of matrix remodeling and perivascular inflammation that further exacerbate the effects of matrix fibrosis and chronic inflammation.